Decrypting the Digital Vault by Understanding Cryptocurrency Adoption Challenges Among Gen Z: Case of Sri Lanka - Senuri Mallawaarachchi; Uvindu Hemachandra; Deshan Jayakody; Uththara Wickramarathne; Anuja Akalanka Lokeshwara; Gayan Chathuranga Bandara (Ianna Journal of Interdisciplinary Studies)
Background: As digital natives, Gen Zs are at the forefront of embracing cryptocurrencies for technological innovation and financial empowerment. This study is part of a larger effort to understand the evolving trends in the world of cryptocurrency, highlighting the need for more research in this area.